Humic acid-assisted synthesis of stable copper nanoparticles as a peroxidase mimetic and their application in glucose detection. Issue 39 (8th September 2015) - Wang, Nan; Li, Bingchen; Qiao, Fengmin; Sun, Jianchao; Fan, Hai; Ai, Shiyun
Abstract : Stable Cu NPs were prepared using humic acid as the reducing and stabilizing agents for application in glucose detection. Abstract : In this report, stable copper nanoparticles (Cu NPs) were prepared through a facile annealing process using humic acid as the reducing and stabilizing agents. The products were characterized by X-ray powder diffraction, scanning electron microscopy and Fourier transform infrared spectroscopy. The prepared Cu NPs show remarkably intrinsic peroxidase-like activity, which can rapidly catalyze the oxidation of the peroxidase substrate, 3, 3′, 5, 5′-tetramethylbenzidine (TMB), in the presence of H2 O2 to produce a blue-color reaction. The detection limit of H2 O2 by Cu NPs can be as low as 1.32 × 10 −7 M. More importantly, the prepared Cu NPs show excellent stability, which can hardly be oxidized even after 6 months. Based on the aforementioned mechanism, a simple, rapid and selective colorimetric method for glucose detection was developed, and the detection limit of glucose was 6.86 × 10 −7 M. This study provides a novel method for the preparation of stable Cu NPs, which may have widespread applications in the detection of glucose in the human body and pear juice.